SUCCESSFUL DIFFERENT TREATMENT IN INTERMITTENT EXOTROPIA: CASE SERIES: Poster Presentation - Case Series - Resident - NASIKA CELIA DENDY; Sesy Caesarya; Primawita O. Amiruddin; Mayasari Wahyu Kuntorini; Feti Karfiati (Majalah Oftalmologi Indonesia, 2023)
Introduction : In intermittent exotropia, management's goals are to diminish deviation by improving fusion control. Case Illustration : Case 1: A 19-year-old woman has complained of squinting and blurred vision since the age of 3 years. The visual acuity of both eyes (OU) was 0.05, with a BCVA of 0.63. Hirschberg's test was exotropia 15o . The exotropia after the cover test (Figure 1A) improved without blinking. The prism cover test was 35 D in near and distance. Patient was diagnosed with exotropia, an intermittent basic type with good control, astigmatism, and myopia compositus OU. Three months after, with refraction correction and occlusion, the Hirschberg test revealed orthotropia (Figure 1B). Case 2: A 7-year-old boy has suffered of squinting and blurred vision from the age of 6 years. The visual acuity of both eyes was 0.63 with a BCVA of 1.0. Hirschberg's test was exotropia 30° (Figure 2A). The prism cover test was 50 D in near and distance. Exotropia intermittent basic type, poor control, and bilateral astigmatism were diagnosed in the patients. The patient had surgery for bilateral lateral rectus recession. Hirschberg test 1 day Postoperatively, orthotropia was present (Figure 2B). Discussion : In exodeviation, control mechanisms relate to therapy compliance and different deviation angles. Intermittent exotropia can be progressive due to loss of fusion control and cause persistent deviation. Conclusion : For patients with exotropia with intermittent good control, non-surgical management can give good results. Surgical management is considered for large angle deviations in patients with poor control.